Interspecific Variation in Bumblebee Performance on Pollen Diet: New Insights for Mitigation Strategies. - Romain Moerman; Nathalie Roger; Roland De Jonghe; Denis Michez; Maryse Vanderplanck (PLoS ONE, 2016)
Bumblebees (i.e. Bombus genus) are major pollinators of flowering wild plants and crops. Although many species are currently in decline, a number of them remain stable or are even expanding. One factor potentially driving changes in bumblebee distribution is the suitability of plant communities. Actually, bees probably have specific nutritional requirements that could shape their floral choices and constraint them in the current context of global change. However, most studies primarily focus on one bumblebee species at a time, making comparative studies scarce. Herein we performed comparative bioassays on three bumblebee species (i.e. Bombus hypnorum, B. pratorum and B. terrestris) fed on three different pollen diets with distinct nutritive content (Cistus, Erica and Salix pollen diets). Micro-colony performance was compared through different developmental and resource collection parameters for understanding the impact of change in pollen diet on different bumblebee species. The evidence suggests that B. terrestris is by far the most competitive species because of its performance compared to the other species, regardless of pollen diet. Our results also highlight a Bombus species effect as pollen diet impacts the micro-colonies in different ways according to the actual bumblebee species. Such interspecific variation in Bombus performance in response to a dietetic change underlines the importance of considering different bumblebee species in mitigation strategies. Such comparative studies are good advice for developing appropriate suites of plant species that can benefit threatened species while supporting stable or expanding ones.